2020
DOI: 10.1021/acs.jpcc.0c03092
|View full text |Cite
|
Sign up to set email alerts
|

Acquirement of Strong Microwave Absorption of ZnFe2O4@SiO2@Reduced Graphene Oxide/PVDF Composite Membranes by Regulating Crystallization Behavior

Abstract: Currently, the microwave absorption materials with high absorbing efficiency are in urgent need to reduce electromagnetic pollution. Herein, the ZnFe2O4@SiO2 core–shell microspheres were synthesized and combined with reduced graphene oxide (RGO) to form the ingenious hierarchical composites (ZnFe2O4@SiO2@RGO), which were used as wave absorbing functional nanofillers of semicrystalline polyvinylidene fluoride (PVDF) matrix. The microstructure and crystallization behavior of ZnFe2O4@SiO2@RGO/PVDF composite membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In Figure 2A, it can be concluded that six relatively strong diffraction peaks appear at 2 θ = 29.9°, 35.2°, 42.8°, 53.1°, 56.6°, and 62.2°, which are assigned to (220), (311), (400), (422), (511), and (440) crystal planes of ZnFe 2 O 4 nanospheres (JCPDS No. 22‐1012) 29 . There are no characteristic peaks of impurities observed, indicating that the prepared ZnFe 2 O 4 nanospheres have high purity and crystallinity 30 .…”
Section: Resultsmentioning
confidence: 88%
“…In Figure 2A, it can be concluded that six relatively strong diffraction peaks appear at 2 θ = 29.9°, 35.2°, 42.8°, 53.1°, 56.6°, and 62.2°, which are assigned to (220), (311), (400), (422), (511), and (440) crystal planes of ZnFe 2 O 4 nanospheres (JCPDS No. 22‐1012) 29 . There are no characteristic peaks of impurities observed, indicating that the prepared ZnFe 2 O 4 nanospheres have high purity and crystallinity 30 .…”
Section: Resultsmentioning
confidence: 88%
“…3, it can be observed that apparent diffraction peaks of ZnFe 2 O 4 , which are well consistent with the ZnFe 2 O 4 (JCPDS card no. 22-1012), 22 the results indicate that ZnFe 2 O 4 with good crystallinity has been successfully prepared. Compared with ZnFe 2 O 4 , the position of ZnFe 2 O 4 @C of the diffraction peak does not change except only the peak intensity decreases after recombination with the C shell.…”
Section: Resultsmentioning
confidence: 88%
“…It is well known that the contribution of pure RGO to EMA performance is mainly due to its dielectric loss, which can lead to impedance mismatch. 44–46 The excellent EMA performance of FFmSR in the current research is mainly due to the conductivity loss caused by the introduction of RGO. The high density free charge movement in RGO generates micro-currents that interact with the electromagnetic wave and thereafter cause conductivity loss and dissipate the electromagnetic wave into heat energy, improving the EMA performance of the composites.…”
Section: Resultsmentioning
confidence: 92%